2012
DOI: 10.1080/13674676.2011.643861
|View full text |Cite
|
Sign up to set email alerts
|

Mental illness and suicide in British South Asian adults

Abstract: South Asians make up about 5% of the UK population. Their rates for mental illness and suicide have been shown by some researchers to be rather lower than that of the total UK population, using a variety of measures, and considering many psychiatric conditions. This paper reviews the literature on the extent of mental illness among British South Asian adults, and explores aspects of their service use, and their attitudes to mental illness. Some distinguishing features of British South Asian mental health are i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 67 publications
1
13
0
Order By: Relevance
“…As hypothesised, British Asians had significantly higher levels of somatic expression of distress than the British sample. This result might be seen to confirm the findings of some earlier studies showing the expression of somatic symptoms of distress to be a common feature of non-western cultures, particularly those from South East Asia which differ significantly among one another (Ineichen, 2012).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…As hypothesised, British Asians had significantly higher levels of somatic expression of distress than the British sample. This result might be seen to confirm the findings of some earlier studies showing the expression of somatic symptoms of distress to be a common feature of non-western cultures, particularly those from South East Asia which differ significantly among one another (Ineichen, 2012).…”
Section: Discussionsupporting
confidence: 87%
“…However, it must be noted that neither British Asians, nor native White Britons are an ethnically or culturally homogeneous group. British Asians studied here may be of Bangladeshi, Indian, or Pakistani origin; they may be agnostics, Christians, Hindus, Sikhs, or Muslims and they be more or less identifiable with their culture of origin (Ineichen, 2012). The same applies to native White Britons who may be from different parts of the British Isles and of different religions.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…As well as a reluctance to seek help from mental health practitioners, a possible explanation for the under-utilisation of services is a low detection rate of CMDs in British SA women in primary care (Ineichen, 2012). There is some evidence that SA women may be more likely to somatise emotional distress than White women (Sproston & Nazroo, 2002), and to link causes of distress to external factors rather than to internal conflict (Malik, 2000).…”
Section: Help-seekingmentioning
confidence: 99%
“…reported that South Asian women older than 65 had the highest rate of suicide among all South Asians and twice the rate of non‐Asians in England and Wales . Other studies have found an increased rate of suicide and suicide attempts in younger South Asian women aged 15–24 in the UK, with intergenerational conflict between more traditional parents and ‘Westernised’ children as the major contributor to this increase …”
Section: Introductionmentioning
confidence: 99%